2D Zeolite Coatings: Langmuir–Schaefer Deposition of 3 nm Thick MFI Zeolite Nanosheets1. (13th April 2015) - Rangnekar, Neel; Shete, Meera; Agrawal, Kumar Varoon; Topuz, Berna; Kumar, Prashant; Guo, Qiang; Ismail, Issam; Alyoubi, Abdulrahman; Basahel, Sulaiman; Narasimharao, Katabathini; Macosko, Christopher W.; Mkhoyan, K. Andre; et al.
Abstract Stable suspensions of zeolite nanosheets (3 nm thick MFI layers) were prepared in ethanol following acid treatment, which partially removed the associated organic structure‐directing agent. Nanosheets from these suspensions could then be dispersed at the air–water interface and transferred to silicon wafers using Langmuir–Schaefer deposition. Using layer‐by‐layer deposition, control on coating thickness was demonstrated. In‐plane X‐ray diffraction (XRD) revealed that the deposited nanosheets contract upon calcination similar to bulk MFI crystals. Different methods for secondary growth resulted in preferentially oriented thin films of MFI, which had sub‐12‐nm thickness in certain cases. Upon calcination, there was no contraction detectable by in‐plane XRD, indicating well‐intergrown MFI films that are strongly attached to the substrate.